Chemical Characteristics of Dried Octopus in Solar-Biomass Hybrid Dryer - Arina Fatharani (Jurnal Teknologi Agro-Industri, 2025)
As the main producing area, processing dried octopus in Kaur Regency still relies on traditional drying methods, which have various weaknesses. This study aims to analyse dried octopus's chemical characteristics (moisture, ash, and fat content) using a hybrid solar-biomass dryer. The experimental design used a Completely Randomised Design (CRD) with two factors, namely wood biomass feed (4 kg and 5 kg) and octopus body parts (head, swim membrane, upper arm, middle arm, and lower arm). The results showed that the moisture content of the final product ranged from 14.83-15.93% and met the SNI 2719-2017 standard (≤20%), without being significantly affected by the treatments given. The ash content (3.33-5.46%) was significantly affected by both treatment factors but still met the quality standard (≤7%), with the highest value in the head. Fat content (10.28-19.11%) was mainly influenced by body part and its interaction with biomass feed, with the highest distribution in the head and swimming membrane.